Dampak Rasio Hutang dan Perputaran Modal Kerja terhadap Harga Saham PT Bekasi Fajar Industrial Estate Tbk Periode 2014-2023 - Badri, Badri; Nuryani, Anum (Universitas Mitra Indonesia, 2024)
This study examines the Share Price of PT Bekasi Fajar Industrial Estate Tbk (BeFa) for the 2014-2023 period which is influenced by factors such as Debt Ratio, Working Capital Turnover and Sales Growth. The data processed is secondary data on DER ratios, WCT, Sales Growth obtained from the Financial Position Report and Profit and Loss Report, as well as the Stock Overview for the closing price of BeFa shares. Next, SPSS was used to analyze the data using multiple linear regression analysis to obtain partial, simultaneous effects and the coefficient of determination. The findings obtained are that partially the Debt Ratio and Sales Growth based on processing results have a negative and significant impact on stock prices. Meanwhile, Working Capital Turnover has a positive impact on share prices. Then together these three independent variables have a significant impact on stock prices. The Adjusted R-Sqaure value shows the ability of these factors to explain the company's share price by 96.1%.